2019
DOI: 10.1128/aac.01043-18
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Functional MKK3/6 and MEK1/2 Homologs from Echinococcus granulosus and Investigation of Protoscolecidal Activity of Mitogen-Activated Protein Kinase Signaling Pathway Inhibitors In Vitro and In Vivo

Abstract: Cystic echinococcosis is a zoonosis caused by the larval stage of Echinococcus granulosus sensu lato. There is an urgent need to develop new drugs for the treatment of this disease. In this study, we identified two new members of mitogen-activated protein kinase (MAPK) cascades, MKK3/6 and MEK1/2 homologs (termed EgMKK1 and EgMKK2, respectively), from E. granulosus sensu stricto. Both EgMKK1 and EgMKK2 were expressed at the larval stages. As shown by yeast two-hybrid and coimmunoprecipitation analyses, EgMKK1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…KEGG pathway analysis further demonstrated that the mRNAs targeted by the miRNAs were mainly involved in the regulation of signal transduction, infectious diseases, and the immune system, which have been widely researched and demonstrated to be associated with the functions of exosomes (Coakley et al, 2015 ). The predicted host target genes are involved in the inflammatory responses, including encoding members of the TNF, TLR, MAPK, and NF-κB signaling pathways, which have previously been documented to modulate cytokines during chronic E. granulosus infection (Refik et al, 2005 ; Tuxun et al, 2015 ; Labsi et al, 2018 ; Zhang et al, 2019 ). Additionally, the most abundant miRNAs were predicted to participate in Th1 and Th2 cell differentiation, Th17 cell differentiation, and IL-17 signaling pathway, and these immune responses occur during E. granulosus infections (Tuxun et al, 2012 ; Labsi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…KEGG pathway analysis further demonstrated that the mRNAs targeted by the miRNAs were mainly involved in the regulation of signal transduction, infectious diseases, and the immune system, which have been widely researched and demonstrated to be associated with the functions of exosomes (Coakley et al, 2015 ). The predicted host target genes are involved in the inflammatory responses, including encoding members of the TNF, TLR, MAPK, and NF-κB signaling pathways, which have previously been documented to modulate cytokines during chronic E. granulosus infection (Refik et al, 2005 ; Tuxun et al, 2015 ; Labsi et al, 2018 ; Zhang et al, 2019 ). Additionally, the most abundant miRNAs were predicted to participate in Th1 and Th2 cell differentiation, Th17 cell differentiation, and IL-17 signaling pathway, and these immune responses occur during E. granulosus infections (Tuxun et al, 2012 ; Labsi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…EGFR-mediated activation of the Ras/Raf/MEK/ERK signaling pathway has been demonstrated in E. multilocularis , and some drugs have been shown to inhibit the activation of the signaling in the parasite ( 13 , 21 , 22 ). U0126 was recently shown to display significant in vitro effect on protoscoleces of the closely related species E. granulosus and reduce, but not significantly, parasite burden in mice ( 23 ). In the present study, U0126 treatment resulted in significantly reduced parasite weight, despite the lower reduction in parasite burden in comparison with BIBW2992 and albendazole treatments.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that miR-71 was significantly highly expressed in NSD and down-regulated in SSD, and suggest that its targets may be involved in the regulation of the MAPK and Wnt signaling pathways in SSD. A recent study proposed that MAPK may be a therapeutic target in E. granulosus through the suppression of MKK3/6 and MEK1/2 (Zhang et al, 2019). Furthermore, some Wnt-pathway related proteins, such as the frizzled receptor eg-fz4, have been shown to be highly expressed in PSC cultured in vitro toward adult maturation, and that they may be involved in early development of the nervous system and gut-derived organs (Pan et al, 2006;Dezaki et al, 2016;Zidek et al, 2018).…”
Section: Mirnas Of E Granulosus As Novel Therapeutic Targets For Parasite Controlmentioning
confidence: 99%